Assessment of the Pharmacokinetic Interaction between Eltrombopag and Lopinavir-Ritonavir in Healthy Adult Subjects - Wire, Mary B.; McLean, Heidi B.; Pendry, Carolyn; Theodore, Dickens; Park, Jung W.; Peng, Bin (Antimicrobial Agents and Chemotherapy, 2012)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC